Perspectives of logistics infrastructure development in Сentral Asia: risk management in Uzbekistan-Kazakhstan joint projects (Journal of Economic Research & Business Administration, 2026)
Logistics infrastructure plays a strategic role in Central Asian integration processes, serving as the foundation for cross-border trade between Kazakhstan and Uzbekistan. In the context of global instability and growing transit flows, a risk-based approach to the implementation of joint infrastructure projects aimed at ensuring their sustainability and long-term economic efficiency is particularly relevant.The purpose of this study is to identify prospects for the development of logistics infrastructure in Central Asia and develop risk management recommendations for joint projects between Kazakhstan and Uzbekistan. The study focuses on the analysis of critical nodes of transport corridors, such as the Darbaza-Maktaaral railway project, and is based on the concept of integrating "hard" infrastructure with "soft" digital solutions to minimize transaction costs.The scientific and practical significance of this study lies in the application of the qualitative and quantitative risk analysis methodology (ISO 31000) to joint logistics initiatives in cross-border areas. The research methods include risk-based modeling, threat factor prioritization using a probability-damage matrix, and key performance indicator (KPI) assessment based on industry data and international reports (CAREC, World Bank).The results show that the transition to decentralized routes and the implementation of digital standards (e-CMR) can reduce border clearance time by 66% and lower the share of logistics costs in the final cost of goods. The study also reveals that realizing the full potential of these projects depends on overcoming institutional incompatibility and synchronizing customs procedures. The results of the study can serve as a guide for government agencies, international investors, and transport operators in planning and implementing cross-border megaprojects in the region. Keywords: logistics infrastructure, risk management, joint projects, Kazakhstan, Uzbekistan, economic efficiency.